2015
DOI: 10.1177/1758834015591952
|View full text |Cite|
|
Sign up to set email alerts
|

Precision medicine in colorectal cancer: the molecular profile alters treatment strategies

Abstract: When considering treatment options for patients with metastatic colorectal cancer (mCRC), molecular profiling has become a pivotal component in guiding clinical decisions. FOLFOX and FOLFIRI (fluorouracuil, leucovorin plus oxaliplatin or ininotecan, respectively) are the standard base regimens used for the treatment of mCRC. Biologic agents, such as the epidermal growth factor receptor (EGFR) targeted therapies, cetuximab and panitumumab and the vascular endothelial growth factor monoclonal antibody, bevacizum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 45 publications
1
40
0
1
Order By: Relevance
“…The treatment paradigm for CRLM is rapidly shifting to a more personalized approach so as to execute precision medicine [31]. In a large, non-randomized study, patients exhibiting factors associated with a high risk of recurrence gained more benefit from adjuvant therapy than those with factors suggesting a low risk of recurrence [32].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment paradigm for CRLM is rapidly shifting to a more personalized approach so as to execute precision medicine [31]. In a large, non-randomized study, patients exhibiting factors associated with a high risk of recurrence gained more benefit from adjuvant therapy than those with factors suggesting a low risk of recurrence [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent analyses has suggested that CRC patients with KRAS G13 mutations benefit from anti-EGFR therapy (Tejpar et al, 2012). This issue continues to evolve (Van Cutsem et al, 2015) because the National Comprehensive Cancer Network recommendation now indicates that CRC patients with any KRAS or NRAS mutation, including those of Q61 and A146, will not benefit from anti-EGFR therapy (Tran et al, 2015).…”
Section: Ras Mutation Hotspots -Structural Biological and Functionalmentioning
confidence: 99%
“…Depending upon the stage, the treatment of colon cancer involves multiple modalities, including surgery, radiotherapy, interventional radiology approaches and systemic chemotherapy. Although targeted therapy drugs for colon cancer have been introduced (2), such as bevacizumab, cetuximab and panitumumab, the prognosis remains unsatisfactory (3,4). Thus, there is still a great clinical need to develop drugs for colon cancer treatment.…”
Section: Introductionmentioning
confidence: 99%